The COVID-19 Pandemic and Atmospheric Nitrogen Dioxide: A perspective on Viral-Environmental Interactions - Emmanuel O. Aiyeyun (IPS Journal of Public Health, 2026)
Background: Coronavirus disease 2019 (COVID-19) pandemic has traditionally been understood as an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, the marked disease pattern, distribution, clinical expression, geographical variation in disease severity, heterogeneity of clinical outcomes, and the strong epidemiological association between ambient nitrogen dioxide (NO₂) pollution and COVID-19 have prompted renewed interest in environmental determinants of disease. A Recent Mendelian randomization (MR) study demonstrating a potential causality between NO₂ exposure and COVID-19 risk provides evidence suggesting that nitrogen dioxide plays a mechanistic role beyond simple confounding. Objective: This paper aims to propose a conceptual two-agent model of the COVID-19 pandemic, in which SARS-CoV-2 acts as the infectious agent, while elevated atmospheric nitrogen dioxide (NO₂) functions as an environmental co-determinant that modifies host susceptibility, disease severity, and clinical outcomes during the pandemic. Method: A comprehensive systematic searches of five electronic databases was conducted (Web of Science Core Collection, Scopus, CAB Abstracts, PubMed, and EMBASE). Given the global and prolonged nature of the pandemic, publications spanning multiple years were included. Eligible studies were peer-reviewed articles reporting clinical, molecular, epidemiological and environmental data relevant to COVID-19 and nitrogen dioxide (NO₂) exposure, with peer reviewed literature prioritized over preprints. Satellite-based Sentinel-5P data were used to map tropospheric NO₂ concentrations over Wuhan, China, and other early epicenters of the COVID-19 pandemic during December 2019 and January 2020 when the pandemic began. Results: By integrating epidemiological, genetic, biological, mechanistic, and environmental evidence, this paper supports the hypothesis that the COVID-19 pandemic represents a dual-agent phenomenon in which SARS-CoV-2 and elevated atmospheric NO₂ interacts to produce and modify the observed disease pattern of the pandemic. Conclusion: This study proposes a dual-agent conceptual framework for the COVID-19 pandemic in which SARS-CoV-2 and elevated atmospheric NO₂ exposure interacts to produce and modify the observed disease pattern of the pandemic. This framework integrates infectious and environmental factors into a unified model that better explains the observed differences in transmission, morbidity, and mortality during the pandemic. There is need for stricter emission controls, cleaner energy policies, and continued multidisciplinary research to prevent similar global health crises in the future.